The Role of Parents Develops Child's Social Emotional Skills - Anita Yus (JURNAL BUNGA RAMPAI USIA EMAS, 2017)
This paper discusses the issue of children's education in families, especially the role of parents in the education of children in the city of Medan. The purpose of this study was to determine the role of parents as social emotional skills coach to help children develop social emotional skills. The sample of this research is 102 children and parents of kindergarten children in Medan City which determined by using area random sampling technique. Social emotional skills data of children were collected using Social Emotional Skills Inventory (SESI) and parental role data as social emotional skill coach were collected using questionnaires. Data were analyzed with descriptive statistics to calculate average score, standard deviation and percentage. The results of the analysis show that, (1) the average achievement of the social emotional skills of the children is in moderate to moderate category, and (2) the role of the parent giving social stimulant is in the low category and in general the parents acting as social emotional skill coach tend to repressive style to the igniter.